Pathogenic agents associated with The two-spotted spider mite, Tetranychus urticae Koch in some cotton field in Al Hassakah Province, Syria - Daher, Ammar Khalaf; Barbar, Ziad; Al-Mohamed, Ismail (Journal of agricultural, environmental and veterinary sciences, 2020)
The two-spotted spider mite, Tetranychus urticae Koch, is a phytophagous pest that can cause significant yield losses in cotton fields, and pathogenic organisms are very important to control them. A study was conducted in some cotton fields at Al-Hassakeh province through season 2019 to survey pathogenic organisms associated with two-spotted spider mite. Results showed the isolation and diagnosis of five types of pathogenic fungi with an infection rate of 13.33% Results showed that five fungal species of 4 genera and one bacteria were identified. The Aspergillus niger was the most frequently isolated fungus with 23.33 % frequency, followed by, Neozygites floridana, Aspergillus terreus, Beauveria bassiana, Penicillium sp. and bacteria Bacillus thuringiensis with a frequency of 18.66, 14.66, 13.33, 6.66 % and 23.33%, respectively. The Results showed that the pathogens played an important role to control the two-spotted spider mite (T. urticae).